2020
DOI: 10.1177/1557988320973826
|View full text |Cite
|
Sign up to set email alerts
|

HPV Vaccine and College-Age Men: A Scoping Review

Abstract: The human papillomavirus (HPV) potentially affects every sexually active man in the United States and Canada. In 2017, the vaccine became publicly funded in Canada for males ages 9–26, and was integrated into school vaccination programs. In 2019, HPV vaccination was recommended as routine for all U.S.-based males and females ages 9 through 26, and a shared decision for adults >26 years; however, since the approval of the vaccine in 2006 for females only, the age and dosing recommendations for males have fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…HPV vaccination for men has been reported to not only inhibit the spread of HPV infection with sexual contact but also prevent HPV-related diseases (Spînu et al, 2021). Therefore, several countries such as Australia recommend HPV vaccination for men to achieve eradication of cervical cancer and HPV-related diseases (Hall et al, 2019;Laserson et al, 2020). In the case of Japan, HPV vaccination for men was covered by the National Health Insurance as of 2020 (MSD, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…HPV vaccination for men has been reported to not only inhibit the spread of HPV infection with sexual contact but also prevent HPV-related diseases (Spînu et al, 2021). Therefore, several countries such as Australia recommend HPV vaccination for men to achieve eradication of cervical cancer and HPV-related diseases (Hall et al, 2019;Laserson et al, 2020). In the case of Japan, HPV vaccination for men was covered by the National Health Insurance as of 2020 (MSD, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, they believed that men are “biologically wired to think more about sex than women are,” thought “males can just be more reckless with their sexual actions,” and considered college women to be “more mature at this point in their lives.” This may consequently cause young men to overlook their vulnerability to negative sexual outcomes. A scope review by Laserson et al (2020) indicated that male HPV vaccine adherence in the United States and Canada is still low among young males ages 18–26 years old. A meta-analysis of 39 studies on knowledge of HPV and HPV vaccine, the intention to vaccinate, and HPV vaccination uptake among male college students also suggested that it is necessary to further increase the knowledge about HPV and HPV vaccine uptake among college men in the United States (Kasymova, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, HPV infection is usually presented as a subclinical form in men, resulting in a large number of asymptomatic carriers. [ 1 2 3 4 5 ] It is frequently observing HPV as a sexually transmitted infection is increasing in Iranian men and Middle East countries. Existing data suggested that diagnosed HR-HPV genotypes might not have clinical manifestations on men.…”
mentioning
confidence: 99%
“…The risk of genital and ano-genital neoplasia in women will have been declining using HPV testing and vaccination of men. [ 1 4 5 ]…”
mentioning
confidence: 99%
See 1 more Smart Citation